Peer Mentoring Training for Students - Farisan Akbar, Rifqi; Damara Sastri, Prinska; Prameswari Putri Djaelani, Bella; Meilia Azzahra, Sandra; Ningsing Handayani Halawa, Wien; Bernadus, Benny; Oktaviani, Fitriana (Universitas INABA, 2024)
Many people experience stress in living their daily lives, including students. Stress is the body's reaction to situations that seem dangerous or difficult. Light stress will be useful because it can spur a person to think and do things faster and harder so they can answer the challenges of everyday life. However, stress that is too much and sustainable, if left untreated, will be dangerous for individuals. Individuals in a state of stress view problems as tangled threads, they have difficulty finding a way out, so they need help. Peer Support is defined as a variety of interpersonal helping behaviors assumed by non-professionals who undertake helping roles with others. This peer mentor aims to overcome someone's stress in academic life in the campus environment. This training method is given in several sessions to students which contain a variety of knowledge and carry out role plays to apply previously obtained knowledge. The training session will close with an implementation questionnaire